Use and exploitation of new technologies in the conservation of built heritage. Review of emblematic cases in Perú - Quinto Fernández, Silvia (2016)
The use and development of new technologies in knowledge, conservation and intervention of the built heritage in Peru is passing through a phase of experimentation and application on specific projects.This review attempts to highlight practical experiences developed in Peru by international, national and private institutes in the conservation of heritage legacy, analyzing the use of different technological sources for digitalization, recreation and virtual representation.The examples are emerging from national affairs and are to be considered in the specialized professional training in built heritage, emphasizing its multidisciplinary nature.